Muddy state development in Ghana’s upper east region: one village, one dam, and its effects on smallholder farmers in a study community - Roan, Patrick, author; Hausermann, Heidi, advisor; Leisz, Stephen, committee member; Fonte, Steven, committee member; Nyantakyi-Frimpong, Hanson, committee member (Colorado State University. Libraries, 2023)
Warming trends and drought conditions across northern Ghana portend major implications for water access critical to the future of smallholder farming, food security, and human health. To mediate the impacts of future water resource concerns, the Ghanaian government launched the One Village, One Dam initiative (1V1D) in 2017 which aimed to construct or repair approximately 570 small-scale dams on ephemeral streams in northern communities. Hundreds of dams have been constructed or overhauled to develop northern regions and provide communities with access to water, particularly for dry season farming. This thesis examines the implications of the 1V1D intervention in one study community in Ghana's Upper East Region including social-ecological relationships between smallholders and their farming practices, land-use changes, gold mining, climate data, and farmer perceptions of climate change. My findings reveal that while the government attempted a community-based approach with 1V1D, local insight was marginalized and implementation relied more on outside engineering expertise and State preferences. Most participants contend the dam embankment was poorly designed, improperly located for adequate water capture, and heavy sedimentation including from gold mining is decreasing its capacity. The dam is insufficient for dry season farming, forcing farmers and livestock to depend on wells and boreholes for water, and regional markets for supplemental food supply. Issues of food, water, and economic insecurity are therefore not well addressed by this State development project. A comparative analysis of participant perceptions on climate change is explored and this thesis ends with insights on community ideas for more sustainable climate adaptation interventions.
Keywords: dams; political ecology; state development; Ghana; agriculture; social-ecology